Experience in Organization as Mediator of Entrepreneurship Education for Entrepreneurship Intention (International Conference of Graduate School on Sustainability (ICGSS), 2021)
The purpose of this research is to describe organizational experience, entrepreneurship education and entrepreneurship intention; analyze the effect of entrepreneurship education on entrepreneurship intention; analyze the effect of entrepreneurship education on organizational experience; analyze the effect of organizational experience on entrepreneurship intention; and analyze the effect of entrepreneurship education on entrepreneurship intention through entrepreneurship interest in students. This research uses explanatory research. The research population is all students of Universitas Merdeka Malang who have received entrepreneurship courses and are active in campus entrepreneurship organizations. This study used a Likert scale questionnaire which was distributed to 100 respondents. Random sampling technique was used to determine the respondents. This study concludes that entrepreneurship education has a significant effect on entrepreneurship intention and organizational experience, a significant influence also occurs on organizational experience on entrepreneurship intention. The research also shows that the indirect effect of entrepreneurship education on entrepreneurship intention through organizational experience is more prioritized and optimal than the direct effect of endogenous variables.